1997
DOI: 10.1002/(sici)1099-1026(199703)12:2<71::aid-ffj620>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of the Essential Oil of Achillea eriophora DC.

Abstract: Ninety constituents (98%) of the essential oil of the leaves and¯owers of Achillea eriophora DC. (Compositae) were identi®ed. The main constituents are 1,8-cineole (34%) and the pinenes (13%). The oil contains only 7% of sesquiterpenes, mainly caryophyllene derivatives. Three new farnesol derivatives were isolated as trace constituents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
1
15
1
Order By: Relevance
“…Plants collected from south Iran (Shiraz) displayed 1,8cineol (34%) as the main essential oil component and contained very little camphor [30]. Santolina alcohol, αthujone and cis-chrysanthenol were found as minor compounds, which could not be detected in the plants from the present study.…”
Section: Achillea Eriophoracontrasting
confidence: 74%
“…Plants collected from south Iran (Shiraz) displayed 1,8cineol (34%) as the main essential oil component and contained very little camphor [30]. Santolina alcohol, αthujone and cis-chrysanthenol were found as minor compounds, which could not be detected in the plants from the present study.…”
Section: Achillea Eriophoracontrasting
confidence: 74%
“…Among Iranian species of Achillea (Table 1), A. eriophora, A. millefolium and A. tenuifolia contained 1,8-cineole and α-pinene and β-pinene as their major aroma components. Weyerstahl et al [9] analyzed A. eriophora collected from Pars Province in Iran and confirmed the same major components in its essential oil fraction. Another investigator [14] reported that camphor was the major volatile compound in the water distillate of flowers of A. tenuifolia which were collected north of Tehran.…”
Section: Gc/ms Analysissupporting
confidence: 86%
“…Many species of Achillea have been analyzed for their bioactives with more than 100 components found, including volatiles (mono-and sesquiterpenes or their lactones) in headspace vapor or essential oils and highermolecular-weight phenolics or flavonoids from the extracts ( [2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]). …”
Section: Introductionmentioning
confidence: 86%
“…One of these identifications was tentative (RI = 1679.4 banca et al, 2004;Stojanović et al, 2005). The high amount of 1,8-cineole (34.2%) has been reported A. eriophora (Weyerstahl et al, 1997). The high amount of sabinene, as we found in our populations 36, 38 and 39 (19.3-35.7%), has been also previously reported (Verma et al, 2017;Nadim et al, 2011;Conti et al, 2010;Boskovic et al, 2005).…”
Section: Essential Oil Compositionmentioning
confidence: 58%